Odpowiedź :
1. Doprowadź do najprostszej postaci
a) 2x-2x(x-3)-(x-2)=2x-2x²+6x-x+2=-2x²+7x+2
b) (3√2-1)(√2+5)=6+15√2-√2-5=1+14√2
c) 8xy(2x-3y+5)-9xy=16x²y-24xy²+40xy
d) 3(-2x+8)-2x(3x-9y+4)=-6x+24-6x²+18xy-8x=-14x+24-6x²+18xy
2. Wyłącz wspólny czynnik przed nawias
a) 15ab-6b=3b(5a-1)
b) 4xyz+10xz=2xz(2y+5)
c) 3xy-9x²y+27x=3x(y-3xy+9)
d) 3 ananasy + 2 banany=anany(3as+2b)
a) 2x-2x(x-3)-(x-2)=2x-2x²+6x-x+2=-2x²+7x+2
b) (3√2-1)(√2+5)=6+15√2-√2-5=1+14√2
c) 8xy(2x-3y+5)-9xy=16x²y-24xy²+40xy
d) 3(-2x+8)-2x(3x-9y+4)=-6x+24-6x²+18xy-8x=-14x+24-6x²+18xy
2. Wyłącz wspólny czynnik przed nawias
a) 15ab-6b=3b(5a-1)
b) 4xyz+10xz=2xz(2y+5)
c) 3xy-9x²y+27x=3x(y-3xy+9)
d) 3 ananasy + 2 banany=anany(3as+2b)
1
a) 2x-2x(x-3)-(x-2) = 2x-2x²+6x-x+2=-2x²+7x+2
b) (3[2]-1)([2]+5)= ?
c) 8xy(2x-3y+5)-9xy= 16xy- 24xy²+40xy-9xy=-24xy²+47xy
d) 3(-2x+8)-2x(3x-9y+4)=-6x+24-6x²+18xy-8x=-6x²+18xy-14x+24
2
a) 15ab-6b
3b(5a-2)
b) 4xyz+10xz
2xz(2y+5)
c) 3xy-9x^2y+27
3(xy-3x²y+9)
d) 3 ananasy + 2 banany
anan(3asy+2by)
a) 2x-2x(x-3)-(x-2) = 2x-2x²+6x-x+2=-2x²+7x+2
b) (3[2]-1)([2]+5)= ?
c) 8xy(2x-3y+5)-9xy= 16xy- 24xy²+40xy-9xy=-24xy²+47xy
d) 3(-2x+8)-2x(3x-9y+4)=-6x+24-6x²+18xy-8x=-6x²+18xy-14x+24
2
a) 15ab-6b
3b(5a-2)
b) 4xyz+10xz
2xz(2y+5)
c) 3xy-9x^2y+27
3(xy-3x²y+9)
d) 3 ananasy + 2 banany
anan(3asy+2by)